School travel mode, parenting practices and physical activity among UK Year 5 and 6 children - Jago, Russell; Wood, Lesley; Sebire, Simon; Edwards, Mark J.; Davies, Ben; Banfield, Kathryn; Fox, Kenneth; Thompson, Janice; Cooper, Ashley R.; Montgomery, Alan A. (BioMed Central, 2014)
Background: